Materials and Methods of Biosensor Interfaces With Stability - Song, Min; Lin, Xiaogang; Peng, Zhijia; Xu, Shibin; Jin, Lifeng; Zheng, Xiaodong; Luo, Haoyue (Frontiers in Materials, 2021)
Biosensor can convert the concentration of biological analyte into an electrical signal or other signals for detection. It is widely used in medical diagnostics, food safety, process control and environmental monitoring fields. In recent years, new schemes of stable biosensor interfaces have attracted much attention. Interface design is a vital part of biosensor development, since its stability can be directly related to the quality of sensing performance such as sensitivity, stability and linearity. This review summarized the latest methods and materials used to construct stable biosensor interfaces, and pointed some future perspectives and challenges of them. From the literature, we found that nanomaterials, polymers as well as their composites such as chitosan, cellulose and conducting polymers are the most common materials used in the biosensor interfaces design. Apart from materials, there are increasing developments in monolayer membranes techniques, three-dimensional constructions and other interface techniques. This review is a study of the latest progress in biosensor interface stability solutions, which may provide some references and innovative directions of biosensor interface design for researchers in biosensor fields, and encourage people to further explore new materials and methods.